A Pragma-Dialectical Study of David Hare’s ‘Stuff Happens (Zien Journal of Social Sciences and Humanities, 2021)
This study analyzes David Hare’s play” Stuff Happens” from pragma-dialectical perspective. The study tries to approach the characters in the light of van Eemeren’s pragma-dialectical Model. The study is put to determine the most frequency fallacy committed by the characters of the plays and to show the most utilized speech acts and how these acts highlight the characters’ own personalities. The study concludes that the speech acts used in the play are an efficient tool in approaching the characters and the model of analysis used is workable on the data under analysis.